2-(Cyclopropylamino)-5-(4-methoxybenzylidene)thiazol-4(5H)-one - Ivan Sydorenko; Serhii Holota; Andrii Lozynskyi; Yulian Konechnyi; Volodymyr Horishny; Andriy Karkhut; Svyatoslav Polovkovych; Olexandr Karpenko; Roman Lesyk (Molbank, 2022)
Multicomponent reactions effectively contribute to modern organic and medicinal chemistry. 4-Thiazolidinone core and cyclopropyl moiety are important structural motifs for design of potential biologically active molecules. In the present paper, the convenient step-economy and cost-effective synthesis of 2-(cyclopropylamino)-5-(4-methoxybenzylidene)thiazol-4(5H)-one (2) is described based on the application of the MCR methodology. The proposed approach includes direct one-pot interaction of 2-thioxothiazolidin-4-one (rhodanine), 4-methoxybenzaldehyde with cyclopropylamine which was used in 10% excess compare to other reagents. The structure of synthesized compound 2 was confirmed using 1H, 13C, 2D NMR, LC-MS, IR and UV spectra. The presence of prototropic amino/imino tautomerism for synthesized compound 2 was observed based on spectral analysis data. Screening of antimicrobial activity against 12 strains of Gram-positive and Gram-negative bacteria, as well as yeasts, was performed for synthesized derivative 2.